2019
DOI: 10.1177/1362361319855795
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital mortality among adults with autism spectrum disorder in the United States: A retrospective analysis of US hospital discharge data

Abstract: A retrospective data analysis using 2004–2014 Healthcare Cost and Utilization Project Nationwide Inpatient Sample was conducted to examine in-hospital mortality among adults with autism spectrum disorders in the United States compared to individuals in the general population. We modeled logistic regressions to compare inpatient hospital mortality between adults with autism spectrum disorders (n = 34,237) and age-matched and sex-matched controls (n = 102,711) in a 1:3 ratio. Adults with autism spectrum disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 56 publications
0
39
0
Order By: Relevance
“…In terms of suggestions for improving access, autistic adults reported ( Table 3) that visiting their doctor would be easier if they could book an appointment online (68.6%, χ 2 =16.2), could book an appointment by text (37.1%, χ 2 =28.62), could book the first or last appointment of the day (40.4%, χ 2 =11.00), could wait in a quiet place or outside until it was their turn (54.5%, χ 2 =213.21) and could email their doctor in advance with a description of the issue they need to discuss (61.1%, 15), in all cases significantly more often than parents or control respondents (p<=0.001). Parents agreed that visiting a doctor would be easier if they could book an appointment online (56.2%, =47.15, p<0.001) were far more likely than control respondents (3.0%) to disagree or strongly disagree that their doctor was knowledgeable about autism.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of suggestions for improving access, autistic adults reported ( Table 3) that visiting their doctor would be easier if they could book an appointment online (68.6%, χ 2 =16.2), could book an appointment by text (37.1%, χ 2 =28.62), could book the first or last appointment of the day (40.4%, χ 2 =11.00), could wait in a quiet place or outside until it was their turn (54.5%, χ 2 =213.21) and could email their doctor in advance with a description of the issue they need to discuss (61.1%, 15), in all cases significantly more often than parents or control respondents (p<=0.001). Parents agreed that visiting a doctor would be easier if they could book an appointment online (56.2%, =47.15, p<0.001) were far more likely than control respondents (3.0%) to disagree or strongly disagree that their doctor was knowledgeable about autism.…”
Section: Resultsmentioning
confidence: 99%
“…Autistic adults experience a greater number of co-occurring physical and mental health conditions than non-autistic adults (Croen et al, 2015;Fortuna et al, 2016), greater healthcare costs (Zerbo et al, 2019), higher rates of premature mortality (Hirvikoski et al, 2016), and higher inpatient mortality rates (Akobirshoev, Mitra, Dembo, & Lauer, 2020). Not surprisingly, studies have also found that autistic adults experience significant healthcare disparities, with higher reported rates of unmet healthcare needs, higher emergency department visits, lower use of preventive services, and lower ratings of patient-provider communication as compared to nonautistic adults (Nicolaidis et al, 2013).…”
Section: Healthcare Provider Self-efficacy Scalementioning
confidence: 99%
“…Enhancing the accessibility of COVID-19 testing, particularly in cases of shortage, has added potential to reduce the proportion of autistic individuals and those with ID who require any treatment, hospitalisation or intensive care. This is significant, given that autistic people and those with ID often have suboptimal experiences of accessing healthcare and hospital admission (13-16) and experience higher odds for inpatient hospital mortality (92).…”
Section: Access To Treatment Hospitalisation and Intensive Carementioning
confidence: 99%